1993
DOI: 10.1128/aem.59.11.3695-3700.1993
|View full text |Cite
|
Sign up to set email alerts
|

Isotactic polypropylene biodegradation by a microbial community: physicochemical characterization of metabolites produced

Abstract: From a selective enrichment culture prepared with different soil samples on starch-containing polyethylene we isolated four microaerophilic microbial communities able to grow on this kind of plastic with no additional carbon source. One consortium, designated community 3S, was tested with pure isotactic polypropylene to determine whether the consortium was able to degrade this polymer. Polypropylene strips were incubated for 5 months in a mineral medium containing sodium lactate and glucose in screw-cap bottle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(76 citation statements)
references
References 21 publications
2
70
0
Order By: Relevance
“…Kaczmarek and Bajer [27] also reported the certain modification and appearance of new peaks in the cellulose blended PVC sample by FTIR analysis. Cacciari et al [42] reported the detection of new signals attributed to propylene structure and also some proton signals in treated sample of polypropylene NMR. In our study NMR results revealed the increase in number of signals in comparison to control, suggesting some chemical change/shifting in the polymeric material.…”
Section: Discussionmentioning
confidence: 99%
“…Kaczmarek and Bajer [27] also reported the certain modification and appearance of new peaks in the cellulose blended PVC sample by FTIR analysis. Cacciari et al [42] reported the detection of new signals attributed to propylene structure and also some proton signals in treated sample of polypropylene NMR. In our study NMR results revealed the increase in number of signals in comparison to control, suggesting some chemical change/shifting in the polymeric material.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, only 10% of the extracted products were identified as hydrocarbons (C 10 H 22 to C 31 H 64 ) that may be derived from the degradation of PP itself. This result indicated that the plasticizers, other than the PP itself, were prone to be degraded by the sandy soil microorganisms (Cacciari et al, 1993).…”
Section: Ppmentioning
confidence: 94%
“…In 1993, microbial degradation of PP was firstly assessed by cultures enriched from sandy soils containing PE wastes (Cacciari et al, 1993). After an incubation period of 175 days, the amount of degradation products, which were extracted with methylene chloride, accounted for 40% of the initial weight of tested PP.…”
Section: Ppmentioning
confidence: 99%
“…They observed the growth of microorganism (Pseudomonas, Erwinia and Bacillus) was rising in the presence of the tested polymers. It has also been stated that these microorganisms are capable of biodegrading not only PCL but also other polymers [36].…”
Section: Biodegradable Polymers For Food Packagingmentioning
confidence: 99%